Synthesis of 3'-thioribonucleosides and their incorporation into oligoribonucleotides via phosphoramidite chemistry. - Sun, S (1997)
Oligoribonucleotides containing 3'-S-phosphorothiolate linkages are valuable probes in nucleic acid biochemistry, but their accessibility has been limited because 3'-thioribonucleoside phosphoramidites have not been available. We synthesized 3'-thioribonucleoside derivatives (C, G, and U) via glycosylations of nucleoside bases with 3-S-thiobenzoyl-5-O-toluoyl-1,2-O-diacetylfuranose 5, which was obtained from 1 ,2-O-isopropylidene-5-O-toluoyl-3-trifluoromethane-sulfonyl-alpha-D-x ylofuranose 2 by SN2 displacement with sodium thiobenzoate. Additionally, a 3'-thioinosine derivative was prepared from inosine via direct modification of the ribose, analogous to the previously reported synthesis of 3'-thioadenosine, except that the intermediate 2',3'-epoxide 9 was first protected as the 5'-O-tert-butyldiphenylsilyl ether prior to subsequent synthetic steps. This hydrophobic silyl group facilitated extraction and isolation of synthetic intermediates. After removal of the protecting groups, the 3'-thionucleosides (C, G, U, and I) were treated with 2,2'-dipyridyl disulfide to protect the free thiol group as a disulfide. The 3'-thionucleosides were converted to the corresponding phosphorothioamidites using procedures analogous to those for standard phosphoramidites. The amino groups of 3'-thiocytidine and 3'-thioguanosine were protected as benzoyl and isobutyryl amides, respectively, and the 5'- and 2'-hydroxyl groups of each nucleoside were protected as dimethoxytrityl and tert-butyldimethylsilyl ethers, respectively. The 3'-thiol group was deprotected by reduction with DTT and phosphitylated to afford analytically pure 3'-S-phosphorothioamidites 15, which were incorporated into oligoribonucleotides by solid-phase synthesis. Chemical assays and mass spectrometry of the synthetic RNA showed that ribose-3'-S-phosphorothiolate linkages were installed correctly and efficiently into RNA oligonucleotides using phosphoramidite chemistry.